Peer Education with Smart Card Effects on the Stigma of HIV/AIDS among Non-HIV Inmates - Anisah, Retno Lusmiati; Andriany, Megah; Sofro, Muchlis Achsan Udji; Piriyasart, Jitlada (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2024)
Inmates with HIV/acquired immunodeficiency syndrome (AIDS) are often exposed to psychosocial problems due to stigma. Limited study proved effect of peer education with smart card on the stigma of HIV/AIDS among non-HIV inmates. The purpose of this study was to know the effects of peer education with smart card method on the stigma of HIV/AIDS among inmates. The study design was pre-experimental design. The sample was 94 male inmates without HIV taken using purposive sampling. The stigma was measured used the Visser Personal and Perceived Community Stigma questionnaire. Non-HIV prisoners was educated regarding using HIV/AIDS Smart Cards, Anti-HIV/AIDS Stigma and Discrimination Cards as well as involving a positive HIV for hand shaking role play. Data were analyzed using the Wilcoxon signed rank test. The results showed significant differences between the pre and post-test on personal and perceived community stigma. The findings recommend for correctional nurses to imply this intervention in preventing the stigma of HIV/AIDS and future studies to examine this intervention toward other outcomes such as discrimination in correctional settings.